Evaluation of the wives of male alcohol dependent patients by a group attidute scale - Mırsal, Hasan; Pektaş, Özkan; Kalyoncu, Ö. Ayhan; Tan, Devran; Beyazyürek, Mansur (Journal of Dependence, 2004)
Objective: Dependence is considered as a disease which necessitates the treatment of all the family members. In this study, the wives of male alcohol dependent patients were evaluated by a “Group Attidute Scale” and their participation in the progression of the treatment was discussed. Method: A group of 160 people who were the wives of the male alcohol-dependent patients in inpatient service were included in the study. These people were evaluated by detailed sociodemographic forms and “Group Attidute Scale”. Results: Most of the wives answered as “yes” the question which mentioned about “cooperation in a group” and the other questions asking for the similar meaning. Conclusion: In this cross-sectional preliminary study, it was shown that “group supporting” was important among the wives of the male alcohol dependent patients.